2013
DOI: 10.17159/2078-516x/2013/v25i1a386
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic posture, shoulder muscle activation patterns and isokinetic strength of semi-professional rugby union players

Abstract: Background. Shoulder injuries are the most severe injuries in rugby union players, accounting for almost 20% of injuries related to the sport and resulting in lost playing hours. Objective. To profile the thoracic posture, scapular muscle activation patterns and rotator cuff muscle isokinetic strength of semi-professional rugby union players. Methods. Using the hand-behind-the-neck and -back methods, we manually tested the range of motion (ROM) of the shoulder joints of 91 uninjured semi-professional rugby uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(38 reference statements)
0
5
0
4
Order By: Relevance
“…The analysis of muscle activity patterns and isokinetic strength of semi professional rugby done by Bolton et al (11) showed that shoulder injuries are the most serious in this sport, accounting for almost 20%…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of muscle activity patterns and isokinetic strength of semi professional rugby done by Bolton et al (11) showed that shoulder injuries are the most serious in this sport, accounting for almost 20%…”
Section: Resultsmentioning
confidence: 99%
“…Os demais estudos com atletas de rúgbi demonstraram resultados similares [32,33,41]. O maior PT dos RI é um resultado esperado, tanto para sujeitos saudáveis como para atletas praticantes de qualquer modalidade esportiva devido à musculatura RI ser mais numerosa, anatomicamente maior e mais forte [42], além de ter um braço de alavanca maior quando comparado aos RE [43].…”
Section: /7unclassified
“…A comparação entre os membros e a análise dos valores da razão RE/RI são informações importantes tanto para a avaliação do desempenho muscular como na prevenção de lesões, pois através da identificação de desequilíbrios musculares é possí-vel realizar uma proposta de intervenção prévia [41,45]. Entretanto, os resultados do presente estudo não Além da comparação entre os membros, a análise dos valores percentuais deve ser considerada e esta deve estar entre 60% e 75% para sujeitos do gênero masculino [44].…”
Section: /7unclassified
See 2 more Smart Citations